SOSIALISASI HAMA DAN PENYAKIT TANAMAN PADI DI KELOMPOK WANITA TANI TUNAS HARAPAN KELURAHAN LIMAU MANIS KECAMATAN PAUH KOTA PADANG - Yulmira Yanti; Hasmiandy Hamid; Nurbailis Nurbailis; Noveriza Hermeria (BULETIN ILMIAH NAGARI MEMBANGUN, 2022)
The Tunas Harapan Women Farmers Group, Limau Manis Village, Pauh District, Padang City is one of the farmer groups that has various problems such as drought, high amount of unused land and far access. The main crop planted during the rainy season is lowland rice, but most of the land becomes idle land during the dry season. Another problem that is often faced during the implementation of cultivation is the problem of pests and diseases which are the cause of low production yields. In terms of fertilization, farmers in this location still use artificial fertilizers (chemical fertilizers) and in terms of pest control, they still use chemical pesticides. One of the main components of the IPM program that can be used to control plant pests and diseases is the use of biological agents. The purpose of this community service activity is to increase public knowledge about pests and diseases that often attack rice plants, resulting in decreased yields and crop failure. The method used is the method of socialization, counseling and direct discussion with farmer groups about pests and diseases that often attack rice plants in the field. The results obtained from this empowerment activity are that the Tunas Harapan KWT farmer group understands various plant-disturbing organisms that attack rice plants, the community knows better how to control it properly, so that it can increase production better